2011
DOI: 10.1007/s00726-011-0969-0
|View full text |Cite
|
Sign up to set email alerts
|

Photorelease of amino acids from novel thioxobenzo[f]benzopyran ester conjugates

Abstract: Aiming at the enhancement of the performance of (9-methoxy-3-oxo-3H-benzo[f]benzopyran-1-yl) methyl ester as photocleavable protecting group for the carboxylic acid function at long-wavelengths, 9-methoxy-3-thioxo-3H-benzo[f]benzopyran-L-valine and L-phenylalanine model conjugates were prepared through a thionation reaction of the corresponding oxo-benzobenzopyrans. These thioxobenzobenzopyran derivatives were subjected to photocleavage reactions in the same conditions as the parent oxo-benzobenzopyrans at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…In particular, our earlier findings on the photolytic release of butyric acid from different naphthoxazole, naphthopyran and oxazole fused pyran cages, revealed that these heterocyclic systems were promising, but the required excitation wavelength was relatively short. In order to develop a system that allows the delivery of butyric acid at longer wavelengths, heterocyclic compounds that showed interesting results with other biomolecules, as previously reported [16,18,24] and new naphthopyrans methoxylated at different positions of the polycyclic ring along with corresponding thionated derivatives, were used in the caging of butyric acid. Photolytic studies to determine the kinetic response of all the ester cages 7-15 were carried out in a Rayonet RPR-100 reactor at 254, 300, 350 and 419 nm in mixtures of methanol or acetonitrile with aqueous HEPES buffer in 80:20 solutions.…”
Section: Photolysis Studies Of Butyric Acid Conjugates 7-15mentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, our earlier findings on the photolytic release of butyric acid from different naphthoxazole, naphthopyran and oxazole fused pyran cages, revealed that these heterocyclic systems were promising, but the required excitation wavelength was relatively short. In order to develop a system that allows the delivery of butyric acid at longer wavelengths, heterocyclic compounds that showed interesting results with other biomolecules, as previously reported [16,18,24] and new naphthopyrans methoxylated at different positions of the polycyclic ring along with corresponding thionated derivatives, were used in the caging of butyric acid. Photolytic studies to determine the kinetic response of all the ester cages 7-15 were carried out in a Rayonet RPR-100 reactor at 254, 300, 350 and 419 nm in mixtures of methanol or acetonitrile with aqueous HEPES buffer in 80:20 solutions.…”
Section: Photolysis Studies Of Butyric Acid Conjugates 7-15mentioning
confidence: 99%
“…Thus, the present work evaluates the behaviour of (acridin-9-yl) methyl, (5-methoxy-3-oxo-3H-naphtho [2,1-b]pyran-1-yl) methyl, (8-methoxy-3-oxo-3H-naphtho [2,1-b]pyran-1-yl) methyl, and [11-oxo-2,3,5,6,7,11-hexahydro-1H-pyrano [2,3-f]pyrido[3,2,1-ij]quinolin-9-yl]methyl groups, in comparison with the well-known o-nitrobenzyl group in the light-induced release of butyric acid. Additionally, bearing in mind that the replacement of a carbonyl by a thiocarbonyl group results in an improvement in the photolytic release [23,24], thionated groups; namely (5-methoxy-3-thioxo-3H-naphtho [2,1-b]pyran-1-yl) methyl, (8-methoxy-3-thioxo-3H-naphtho [2,1-b] pyran-1-yl) methyl, and (9-methoxy-3-thioxo-3H-naphtho [2,1-b] pyran-1-yl) methyl were tested. The ester cages, in two solvent systems (methanol or acetonitrile in 80:20 mixtures with HEPES buffer), were irradiated at 254, 300, 350 and 419 nm in a photochemical reactor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, extension of the coumarin aromatic system, resulting in polyaromatic analogues has been found to enhance fluorophoric properties relative to those species lacking aromatic expansion. [27][28][29]31,33,34] Our previous work on photolytic release of butyric acid from different naphthoxazole, naphthopyran (benzocoumarin) and oxazole fused pyran cages has provided insight into both the photophysical and photolysis behaviours of such systems. [33,34] The convenience of benzocoumarins as photoremovable protecting groups, the desire to explore and extend possible applications of these moieties, and interest in making structural alterations to improve their performance, resulted in the present work.…”
Section: Photolysis Studies Of Butyric Acid Conjugates 3a-3ementioning
confidence: 99%
“…[20][21][22][23][24][25][26] In this regard, we have recently reported on benzocoumarins, thio(benzo)coumarins, coumarin fused with julolidine or benzoxazole moieties, and their nitrogen counterparts, namely quinolones, benzoquinolones and thioquinolones. [27][28][29][30][31][32] Considering our previous experience in the field of fluorescent photoactivable molecules based on aromatic and heteroaromatic skeletons for the release of several biomolecules, and previous work regarding butyric acid, [33,34] a new set of amino-substituted benzocoumarin (trivial name for naphthopyran) cages were synthesized. The use of these heterocyclic moieties enables the photorelease of butyric acid at longer wavelengths that are amenable to bio-applications, as a result of the longer absorption maxima.…”
Section: Introductionmentioning
confidence: 99%